SOME ASPECTS OF THE BIOLOGY OF LACTARIUS LACTARIUS (SCHNEIDER) - Rao, T Appa (Indian Journal of Fisheries, 2011)
AMONG the lesser known fishes of India, the big-jawed jumper Lactarius laQfrnius^ .(Schn.) is a prized table fish. Sometimes when there are heavy- catches it is also cured. From Madras, Chid mb ram and y^nkataraman. (1946) and Devaresaii Â£ird Chidambaram (1953) gave brief notes on the food of this species. Further Chacko (1949), Venkataraman- (I960) and Bas^eeruddin and Nayar (1961) mentioned the items .found in the stomach contents of this species from the coastal waters of Gulf of Mannar, Malabar and Madras respectively. The present paper deals -with the observations made by the author, on food and feeding habits, size at maturity, maturation and spawning, sex ratio, fecundity, growth and length-weight relationship of this spa;ies off Waltair during the period ’ 1959-60.